2023
DOI: 10.1007/s13659-023-00387-y
|View full text |Cite
|
Sign up to set email alerts
|

Terpenes extracted from marine sponges with antioxidant activity: a systematic review

Abstract: Marine biodiversity has emerged as a very promising resource of bioactive compounds and secondary metabolites from different sea organisms. The sponge’s secondary metabolites demonstrated various bioactivities and potential pharmacological properties. This systematic review of the literature focuses on the advances achieved in the antioxidant potential of marine sponges in vitro. The review was performed in accordance with PRISMA guidelines. The main inclusion criterion for analysis was articles with identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
(263 reference statements)
0
3
0
Order By: Relevance
“…The obtained IC 50 values were in the order BHT < ASHEO ( Figure 8 ). The potent antioxidant activity of ASHEO could be attributed to its high terpene content, 45 mainly monoterpene hydrocarbons and oxygenated monoterpenes, as determined earlier. These compounds can donate protons to stabilize free radicals.…”
Section: Discussionsupporting
confidence: 58%
“…The obtained IC 50 values were in the order BHT < ASHEO ( Figure 8 ). The potent antioxidant activity of ASHEO could be attributed to its high terpene content, 45 mainly monoterpene hydrocarbons and oxygenated monoterpenes, as determined earlier. These compounds can donate protons to stabilize free radicals.…”
Section: Discussionsupporting
confidence: 58%
“…Besides the two mimicking enzyme activities, CeLutNCs were able to scavenge more than 48% of • OH with a concentration up to 160 μg mL –1 (Figure d). To further investigate the ROS-eliminating capabilities of CeLutNCs, the total ROS scavenging ability was assessed using 1,1-diphenyl-2-picrylhydrazyl radical (DPPH • ), a nitrogen radical containing a number of unpaired electrons . As depicted in Figure e, more than 83% of DPPH • was eliminated by a very low concentration of CeLutNCs (20 μg mL –1 ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…In recent years, a series of literatures published in Natural Products and Bioprospecting showed that MNPs including Ascidians [ 172 ], brown algae [ 173 ], invertebrates [ 174 ], soft corals [ 175 ], some marine animals and creatures (e.g., salmon, shrimp, trout, krill, crayfish, microalgae Heamatococcus pluvialis, Chlorococcum, Chlorella zofingiensis) [ 176 ], and marine sponges [ 177 ] have exhibited a strong antimicrobial activity [ 173 ], with important and potentially bioactive compounds [ 174 ], for example, Astaxanthin [ 176 ], Cembranoids [ 175 ], and Terpenes [ 177 ], and have a broad range of biological activities, and present a huge potential for the development of various drugs for its remarkable bioactivities against mNCDs (such as CVD, cancer, diabetes, neurodegenerative and immune disorders, and others) due to a series of anti-aging [ 178 ], antioxidant, anti-inflammatory, anti-cancer, anti-diabetic, anti-obese, anti-viral (COVID-19 infection), neuro- & nephro-protective, and fertility-enhancing properties. Here, this article also summarized MNPs-derived bioactive compounds and/or targets, their chemical structures, and related potentials on human diseases (Table 2 ).…”
Section: Mechanisms Linked To Human Immunity and Future Prospectsmentioning
confidence: 99%